FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS SUMBER DAYA MANUSIA DI SEKOLAH MENENGAH KEJURUAN NEGERI 4 BENGKULU SELATAN - Farizal, Hendri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The quality of human resources in an organization, including school organizations, is influenced by various factors such as education, training and experience. Therefore, in this research the author focuses on aspects related to the quality of human resources. Qualifications include education, training and experience. This research is a quantitative research with 30 respondents as employees of SMK Negeri 4, and the analytical tools used are multiple linear regression analysis, truncated analysis and t test. The aim of this research is to determine the effect of education, training and experience on the quality of DM at SMK Negeri 4. It is assumed that education, training and experience will influence the quality of human resources at SMK Negeri 4. The research results found that education, training and experience have a positive effect on quality of human resources at SMK Negeri 4 South Bengkulu. Hypothesis testing is based on multiple linear regression and t test. This proves the hypothesis formulated above.